Mengukur Keefektifan Teori Konstruktivisme dalam Pembelajaran - Saputro, M. Nugroho Adi; Pakpahan, Poetri Leharia (JOEAI (Journal of Education and Instruction), 2021)
The purpose of this research is to find out how the implementation of constructivism theory in learning at the secondary school level and to determine the effectiveness of constructivism theory in learning. The research method used is qualitative with a library research approach (literature study). Meanwhile, the measuring instrument used in this study is the essence of constructivism learning theory and the efficiency of classroom learning. Data is collected from relevant data sources such as books, articles, journals that examine the issues under study, data analysis is carried out by organizing data, describing it into units, synthesizing, arranging into patterns, choosing which ones are important and which will be studied and draw conclusions that others can understand. The results obtained show that the implementation of constructivism theory in education can be practised with various models, including a learning model with basic problems and an inquiry learning model. Because these two learning models are considered to be more effective and efficient in developing children's cognitive to construct their cognitive building and it is assessed that children will be more able to understand what they are learning. In conclusion, constructivism theory is very effectively implemented in learning. because constructivism theory provides opportunities for every student to build their knowledge without having to get knowledge from the teacher in their class. So that each student can get more knowledge for himself. Keywords: Effectiveness, Constructivism Theory, Learning